2023
DOI: 10.1108/bpmj-07-2022-0310
|View full text |Cite
|
Sign up to set email alerts
|

Open innovation, enterprise value and the mediating effect of ESG

Abstract: PurposeThis paper aims to investigate the impact of open innovation (OI) in Chinese enterprises on enterprise value (EV). At the same time, this research explores the effects of OI in environmental, social and governance (ESG) and also reveals the intermediary role of ESG in the impact of OI on improving EV.Design/methodology/approachThis study builds a theoretical framework to define a set of hypotheses verified in empirical research. Based on the panel data of Chinese listed companies removing missing data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Academic attention to the adoption and adherence to sustainability/SDG goals and strategies in Asian contexts has been increasing. Scholars have started to look at the role of investor commitment (Liu et al , 2023), corporate reputation (Dash and Sandeep, 2023) and open innovation and entrepreneurial practices (Luan and Xiao, 2023) on CSR-led competitiveness and sustainability performance of firms. However, significant attention is required on this front to help societies and firms address one of the most important challenges posed to mankind in the form of climate change.…”
Section: Resultsmentioning
confidence: 99%
“…Academic attention to the adoption and adherence to sustainability/SDG goals and strategies in Asian contexts has been increasing. Scholars have started to look at the role of investor commitment (Liu et al , 2023), corporate reputation (Dash and Sandeep, 2023) and open innovation and entrepreneurial practices (Luan and Xiao, 2023) on CSR-led competitiveness and sustainability performance of firms. However, significant attention is required on this front to help societies and firms address one of the most important challenges posed to mankind in the form of climate change.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, Ref. [28] found no connection between environmental performance and corporate profitability, indicating that environmental performance may not always result in better financial results.…”
Section: Empirical Review and Hypotheses Developmentmentioning
confidence: 97%
“…Huh et al (2022) [101] examined the structural relationship between ESG management, corporate reputation, and financial performance and found that all components of ESG management had a significant and positive impact on corporate reputation. Luan and Wang (2023) [102] However, Almulhim and Aljughaiman (2023) [104] revealed that firms with more ESG activities tend to have negative financial performance. In Yang et al [105], among ESG activity variables, only governance was found to have a significant negative impact on financial performance, and environmental and social variables were found to have no significant impact on financial or non-financial performance.…”
Section: Esg Managementmentioning
confidence: 99%